The effect of repeated alkali pretreatments on the morphological characteristics of cellulose from oil palm empty fruit bunch fiber-reinforced epoxy adhesive composite - Sukmawan, Romi; Kusmono, Kusmono; Rahmanta, Anugrah Perdana; Saputri, Lestari Hetalesi (Elsevier Ltd., 2022)
In this study, the effect of low-concentration (4 wt) alkali and bleaching pre-treatments on the fibrillation of oil palm empty fruit bunch (OPEFB) fibers were evaluated. The OPEFB fibers were subjected to repeated weak alkali treatment and bleached by hydrogen peroxide in alkaline solution. Fibrillation was accomplished via mechanical process by a household blender. The obtained cellulose morphology was used to find paper-like sheets that were coated with epoxy resin to produce composites by sheet lamination. Fourier-transform infrared spectroscopy revealed that hemicellulose and lignin were partially removed and fiber dispersion strongly depended on the number of alkali treatment cycles. Scanning electron microscopy showed that fibers that underwent 12 alkali treatment cycles presented the most effective fibrillation. In addition, the blender fibrillation of cellulose fibers in a mild (6 wt) alkali solution required less energy than blending in a neutral aqueous medium and improved fibrillation into nanofibrils. The obtained average diameters of the microfibrils and nanofibrils were approximately 7 μm and 89 nm, respectively. The tensile strength and Young's modulus of the composites were approximately 3.6 and 20 times higher, respectively, than those of neat epoxy resin. The proposed chemo-mechanical method could facilitate the use of micro-nanofibrils extracted from OPEFB for fiber-based materials and polymeric composites. © 2022 Elsevier Ltd